Makna Zaqqum Dalam Alquran: Kajian Tafsir Mawdu’i - Iha Fariha; Didi Junaedi; Lukman Zain (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
Hell torture is not only in the form of just hell fire and scorpion, however there is also torture hell which in form of fruits or food which are hardly known by many people. In hell there are food and trees of drink as dish to all residents of hell. Among them, there are trees of zaqqum, trees of dhari, ghislin, al-hamim, al-ghassaq, and al-shadid. This undertanding rises several questions: 1) How is the conception of Zaqqum in the Interpretation of Maudu’i? and 2) How are the interpretation and the view of Moslem Scholars About Zaqqum?. This Research is qualitative and it studies the primary and the secondary book containing the word of zaqqum and about interpretation of maudh`?. The approach of this research is thematic. The result of the research are: 1) According to the interpretation of Maudu’i, Zaqqum is tree for food to dweller of hell, and can also be interpreted as every food bringing lethal. It is likely a very bitter and rotten fruit as well as capable to destroy the throat of the one who eat it. Zaqqum is also interpreted as a boiling oil dirt and represent food of badi sinner 2) The Moslem scholars view and interpretation about zaqqum come from Ahmad Musthafa Al-Maraghi that Allah make tree of zaqqum as temptation and test to infidel pe